International Monitoring Mechanisms for the Implementation of the Convention on the Protection of the Rights of all Workers Migrants and Members of their Families - Djenidi, Mabrouk (Journal of Legal Studies and Researches, 2021)
The Convention on the Protection of the Rights of all Migrants Workers and Members of their Families is concerned with migrants who work outside. It provides protection for workers and members of their families’ rights. The focus in this study will be on defining the Convention and to highlight International Control Mechanisms for the Implementation of its Provisions, through clear procedures, the Reporting System and the Complaints System are both types of reporting and Complaints system.